Book Review: Technology and Experimentation in Archaeology by Sara Cura et al - Silje Bentsen (EXARC, 2021)
Are chaîne opératoire, technology, and experimental protocols and methodology keywords to your research interests? Technology and Experimentation in Archaeology provides international perspectives and excellent case studies on those very subjects.